PEMETAAN KESELARASAN AKTIVITAS TRIDARMA PROGRAM STUDI TEKNIK INDUSTRI UNIVERSITAS ISLAM INDRAGIRI DALAM PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Khairul Ihwan (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
Industrial engineering is one of the engineering science which studied on design coverage, maintenance and integral system installation that consisted of human, material, energy, output equipment and information. Industrial engineering became inseparable from Sustainable Development Goals (SDGs) term No One Left Behind. The purpose of the study is to map TRIDARMA activities by Industrial Engineering study program of Islamic University of Indragiri to SDGs indicators. Primary documents which is studied is Form documents of Industrial Engineering Study Program of Islamic University of Indragiri year 2017; Academic Guidebook, Strategic Plan of Industrial Engineering Study Program of Islamic University of Indragiri, Strategic Plan Documents of Industrial Engineering Study Program of Islamic University of Indragiri and Operational Plan Documents of Industrial Engineering Study Program of Islamic University of Indragiri. Based on desk review, it can be concluded that the Industrial Engineering Study Program of Islamic University of Indragiri could provided the achievement acceleration of 7 goals, 9 targets and 10 SDGs indicators.